Genetic diversity in tomato (Solanum lycopersicum) genotypes - Ahmed, S; Quamruzzaman, AKM; Uddin, M Nazim; Chowdhury, MJ (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 31-36